A Relação entre o Estado, Organismos Internacionais e Instituições Privadas na proposição de Políticas Educacionais - Pereira, Taisa Carla (2019)
This research deals with the public-private partnerships resulting from the relationship between the Brazilian State and private institutions. Based on documentary and bibliographical research our research is systematized in three chapters: In the first chapter, we aim to understand the political, historical and economic context in which this relationship was produced. In the second chapter we discuss the materialization of this perceived relationship in the different forms of public-private partnerships and how these partnerships are being recommended by international organizations as a new type of management to be diffused. Also in this chapter we present the posture of permissiveness and summons made by the public power to the private initiative through the Public Call Records. In the last chapter of the dissertation we bring evidences that prove the existence of the relationship between the Brazilian State and the private institutions mainly in the field of Teacher Training